Aerodynamic - Brandt, Steven A.; American Institute of Aeronautics and Astronautics (Virginia : American Institute of Aeronautics and Astronautics, 2004)
provides documentation and videos related to aerospace and aerodynamics
System requirements: Pentium III or better and 128 RAM. Microsoft Office XP and a web browser like Netscape or Microsoft IE.
Keywords: Space shuttle; Aeronautics; Astronautics